Applicability of an Ionic Liquid Electrolyte to a Phosphorus‐Doped Silicon Negative Electrode for Lithium‐Ion Batteries. Issue 4 (25th January 2019) - Yodoya, Shuhei; Domi, Yasuhiro; Usui, Hiroyuki; Sakaguchi, Hiroki
Abstract: We investigated the applicability of an ionic liquid electrolyte to a phosphorus‐doped Si (P‐doped Si) electrode to improve the performance and safety of the lithium‐ion battery. The electrode exhibited excellent cycling performance with a discharge capacity of 1000 mA h g −1 over 1400 cycles in the ionic liquid electrolyte, whereas the capacity decayed at the 170th cycle in the organic electrolyte. The lithiation/delithiation reaction of P‐doped Si occurred a localized region in the organic electrolyte, which generated a high stress and large strain. The strain accumulated under repeated charge‐discharge cycling, leading to severe electrode disintegration. In contrast, the reaction of P‐doped Si proceeded uniformly in the ionic liquid electrolyte, which suppressed the electrode disintegration. The P‐doped Si electrode also showed good rate performance in the ionic liquid electrolyte; a discharge capacity of 1000 mA h g −1 was retained at 10 C . Abstract : A P‐doped Si electrode exhibited excellent cycling performance with a discharge capacity of 1000 mA h g −1 over 1400 cycles in an ionic liquid electrolyte, whereas the capacity decayed at approximately the 170th cycle in an organic electrolyte. It is concluded that the ionic liquid electrolytes could be successfully applied to a P‐doped Si electrode and that they represent one type of promising electrolyte for next‐generation LIBs with this electrode.